2009
DOI: 10.1111/j.1526-100x.2008.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Rainforest Fragments: Survival of Mixed‐Native Species Seedlings under Contrasting Site Conditions in the Western Ghats, India

Abstract: Historical fragmentation and a current annual deforestation rate of 1.2% in the Western Ghats biodiversity hotspot have resulted in a human-dominated landscape of plantations, agriculture, and developed areas, with embedded rainforest fragments that form biodiversity refuges and animal corridors. On private lands in the Anamalai hills, India, we established restoration sites within three rainforest fragments (5, 19, and 100 ha) representing varying levels of degradation such as open meadow, highly degraded sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 24 publications
2
39
0
1
Order By: Relevance
“…Similarly, several previous studies conducted in tropical areas have demonstrated that some later successional species can perform well in open sites (e.g. [27, 34, 65, 66]). These findings indicate that with careful selection, some later successional species can be incorporated into restoration plantings.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, several previous studies conducted in tropical areas have demonstrated that some later successional species can perform well in open sites (e.g. [27, 34, 65, 66]). These findings indicate that with careful selection, some later successional species can be incorporated into restoration plantings.…”
Section: Discussionsupporting
confidence: 57%
“…The species is often planted around Hindu and Jain temples. In addition, the plant has been identified as a well performing primary tree species in reforestation and restoration projects throughout South and South Eastern Asia (Hoque et al, 2004;Raman et al, 2009;Bhatt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first year of planting is considered a period of sapling adaptation to the adverse conditions present at the site being revegetated, and is therefore when seedlings present higher mortality (Mcdonald et al, 2003;Raman et al, 2009). The decrease in survival rates over the first year of evaluation may also be related to the climatic conditions of the region, since the rains are concentrated in the months of November to January .…”
Section: Discussionmentioning
confidence: 99%